Cloning and characterization of DNA sequences complementary to messenger ribonucleic acids coding for the synthesis of two surface antigens of Trypanosoma brucei. - Pays, E (1980)
Full length double-stranded complementary DNAs (ds cDNAs) could be synthesized on mRNAs enriched in sequences coding for the synthesis of the variant specific antigens (VSAs) AnTat 1.1 and AnTat 1.8 from Trypanosoma brucei brucei. The size of these ds cDNAs is about 1700 and 1850 base pairs for AnTat 1.1 and AnTat 1.8 respectively. The ds cDNAs were cloned in the plasmid pBR322; two clones harboring a copy of each coding sequence were selected. Both the hybrid-arrested translation and the positive hybridization elution methods confirmed that these recombinants contain VSA-specific inserts. A restriction map was constructed in each case. The two sequences seem to be inserted in a reversed 3'--5' orientation, respective to the plasmid polarity. The AnTat 1.8 cloned sequence is a palindrome probably due to a cloning artefact. Hybridization of the cloned DNAs with "Northern" blots of total or poly(A)+ RNA revealed in each case a single, specific band. The expression of these VSA genes appears thus to be regulated at the transcriptional level.